2017
DOI: 10.33549/physiolres.933808
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Expression of Leading and Passenger Strand of miR-21 and miR-16 in Human Colorectal Cancer and Adjacent Colonic Tissues

Abstract: miRNAs are small regulatory RNA molecules involved in post-transcriptional gene silencing. Their biosynthesis results in the formation of duplex consisting of a leading and a passenger strand of mature miRNA. The leading strand exhibits the main activity but recent findings indicate a certain role of the passenger strand as well. Deregulated levels of miRNA were found in many types of cancers including colorectal cancer. miR-21 and miR-16 were indicated as possible markers of colorectal cancer, however, small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…In contrast, miR-16 was upregulated in CT and S, particularly in the LOW grade and no-Met patients, suggesting that high level of miR-16 in cancer tissues is an early diagnostic marker of CRC. This is consistent with several studies that have reported high levels of miR-16 in CRC tissues [60] and/or its association with overall survival [61,62], but in contrast to other studies that have reported its downregulation in CRC [63]. Because this miRNA was downregulated in all CSC types, its reduced expression in patients with CRC could be a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, miR-16 was upregulated in CT and S, particularly in the LOW grade and no-Met patients, suggesting that high level of miR-16 in cancer tissues is an early diagnostic marker of CRC. This is consistent with several studies that have reported high levels of miR-16 in CRC tissues [60] and/or its association with overall survival [61,62], but in contrast to other studies that have reported its downregulation in CRC [63]. Because this miRNA was downregulated in all CSC types, its reduced expression in patients with CRC could be a marker of poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…By comparison of the miRNA transcriptomes of males and females, it was revealed that there are 73 female-biased and 163 male-biased miRNAs in the human circulation and tissues [ 27 ]. A difference in miRNA expression was also observed in colorectal cancer (CRC) tissue [ 9 , 28 , 29 ]. A reason for this finding has not been completely elucidated; however, it does not seem to be associated with the location of miRNAs on sex chromosomes [ 27 ].…”
Section: Biogenesis Of Mirnamentioning
confidence: 99%
“…The second miRNAs strand, the so-called passenger strand, is present in the cytoplasm at much lower concentration compared with the guide strand and, in spite of its low concentration, can be to some extent also incorporated into the RISC [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant difference in miR‐21 expression was observed between metastatic and nonmetastatic tumors (Jepsen et al, ). Recently, it has been reported that the miR‐21 expression pattern has gender‐dependent differences, with higher levels in men compared with women (Hasakova et al, ). Investigation of miR‐21 levels in serum of patients with CRC before and after undergoing curative surgery revealed that miR‐21 concentration is significantly high in preoperative serum and decreases in postoperative patients that underwent curative surgery.…”
Section: The Clinical Value Of Mir‐21 In Crcmentioning
confidence: 99%